Medical education and post pandemic challenges: where are we now? - Valeria Vásquez Estrada; Alejandro Hernández Martínez; Lina María Martínez Sánchez (Revista Internacional de Educação e Saúde)
INTRODUCTION: The COVID-19 pandemic was a shifting point regarding many aspects. Medical education was heavily impacted by this worldwide phenomenon, and nowadays, as it tries to recover from those hard times and go “back to normal”, it is faced with new issues and challenges as neither students nor teachers are the same as before. However, both issues and challenges present as opportunities for improvement, and creative solutions are encouraged. OBJECTIVE: The authors aim to present an overview of post-pandemic challenges in medical education and possible solutions and resources. METHODS: A bibliographic search was carried out in online databases such as ERIC (Education Resources Information Center), LILACS, PubMed, and Google Scholar using MeSH terminology keywords. Articles that best correlated with the objective were selected to be presented in a narrative review. RESULTS: The use of Information and Communication Technologies (ICT), the change in teaching methodologies, and the mental health and soft-skills impact of the pandemic are some of the main issues that medical education is facing after COVID-19. Emerging tools may be useful for both teachers and students to face such matters. CONCLUSION: The COVID-19 pandemic created new challenges for both students and educators, not only on the technical and academic levels but also on the personal and emotional spheres. These challenges are presented as opportunities for improvement as we transition to post-pandemic times.